Nursing Home Survey on Patient Safety Culture: Cross-cultural Validation Data From Spanish Nursing Homes. Issue 4 (7th June 2021) - Vrotsou, Kalliopi; Pérez-Pérez, Pastora; Alías, Gorka; Machón, Mónica; Mateo-Abad, Maider; Vergara, Itziar; Silvestre, Carmen
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: Developing an adequate patient safety culture is a relevant objective for all health care levels. The Nursing Home Survey on Patient Safety Culture (NHSOPS) is a 12-dimension tool assessing safety culture in nursing homes (NH) for elder people. The psychometric properties of its Spanish adaptation are evaluated in this study. Methods: Nursing homes with 15 beds or more, located in the Basque Country (North Spain), were invited in the study. All staff types were allowed to participate. Internal consistency was tested with Cronbach's α. Convergent and divergent validity with Spearman's correlations. Two-sample t test was used for known-groups validity. The NHSOPS dimensionality was tested with confirmatory factor analysis (CFA), and its stability in consecutive administrations (test-retest) was explored. Results: Five hundred fifty-three valid baseline and 83 retest replies were received. The data suggest that the NHSOPS can be represented by a 10-factor model. Two items (A6 and A10) had loadings of less than 0.12. The rest survey items obtained loadings of greater than 0.40. Estimated correlations supported the convergent and divergent validity of the survey. Managers and administrators, as well as staff considering their NH to be a safe place for residents, obtained higher NHSOPS scores, suggesting acceptable known-groups validity. On the other hand, test-retest variation was considerable. Conclusions: The current data support a simpler model, similar to that of the Norwegian NHSOPS validation. The stability of the scale should be further assessed in a bigger sample. Test-retest reliability and developing an adequate scoring scheme are issues worth of further study.